Case Reports in Pediatric Dentistry Journals: A Systematic Review about Their Effect on Impact Factor and Future Investigations - Romeo Patini; Edoardo Staderini; Andrea Camodeca; Federica Guglielmi; Patrizia Gallenzi (MDPI AG, 2019)
Background: The effects of publishing case reports on journal impact factor and their impact on future research in pediatric dentistry has not been clearly evaluated yet. Aim. To assess the relevance and role of case reports in pediatric dentistry. Methods: A systematic review (PROSPERO registration number: CRD42018108621) of all case reports published between 2011 and 2012 in the three major pediatric dentistry journals was performed manually. Data regarding citations of each report were acquired from the Institute for Scientific Information database available online. The authors analyzed information regarding citations (number, percentage, and mean) received by each case report and considered their relation with the 2013 journal impact factor. Results: Case reports accounted for almost sixteen per cent of all articles published between 2011 and 2012. The citation rate of case reports was generally low and the highest mean citation was 0.5. This review revealed that 6 (9.52%) case reports had at least 5 citations and that the majority of the citing articles were also case reports (27.78%) or narrative reviews (25%). Conclusions: The publication of case reports affected the journal impact factor in a negative way, this influence is closely related to the percentage of the published case reports. Case reports about innovative topics, describing rare diseases, syndromes, and pathologies were more frequently cited.